Using macrobenthic community structure and biotic indices to assess the ecological status of Wulan Estuary, Demak, Indonesia - RETNO HARTATI; WIDIANINGSIH WIDIANINGSIH; MUHAMMAD ZAINURI; YUSLI WARDIATNO (Society for Indonesian Biodiversity, 2024)
Abstract. Hartati R, Widianingsih W, Zainuri M, Wardianto Y. 2024. Using macrobenthic community structure and biotic indices to assess the ecological status of Wulan Estuary, Demak, Indonesia. Biodiversitas 25: 3073-3087. Estuaries provide critical habitats for species, and they are valued commercially, recreationally, and culturally. They also filter for sediments and pollutants from rivers before entering the ocean, providing cleaner waters for marine biota. This study presents a unique approach to assessing the ecological status of an estuary using microbenthic community structure and biotic indices with a case study of Wulan Estuary, Demak District, Central Java Province, Indonesia. AZTI’s Marine Biotic Index (AMBI) community structure and biotic indices were used to assess ecological quality at eleven stations and determine the marine macrobenthic fauna's sensitivity to disturbances in two periods, i.e. August 2021 and 2022. A distinct spatial and temporal variation was evident in the macrobenthic community structure, where higher species richness and density were observed in 2022, with some species being more dominant in 2022. The trophic structure analysis showed the dominance of deposit-feeding bivalves in the fine sediments during those sampling intervals. These trophic groups, however, were dispersed less uniformly in the sandy substratum. Compared to the previous year, the density of herbivorous grazers and suspension feeders was higher in 2022. It is also shown by AMBI values that Wulan Estuary belonged to the good (slightly disturbed) to the high (undisturbed) condition, along with other biotic indices, which showed an enhanced habitat quality for benthic organisms. This result revealed the comparative ecological quality of related estuary ecosystems in Indonesia.